(untitled) (Repertorio Científico, 2021)
This research shows the results of a study based on technological vigilance, comparative papers and foresight perspective, dealing with the advances and gaps for the implementation of the supply chain for the development and future uses of the offshore wind energy in Costa Rica. This emerging economy has stood out, internationally, for assuming and leading significant commitments to the SDGs, climatic actions and decarbonization of the economy. Therefore, it is essential to maintain the 100% renewable energy vision, but also to encourage the addition, in diversified and progressive way, of non-conventional energy, such as offshore wind. The findings confirm the multiple and significant challenges that must be overcome for the planning, construction and operation of offshore wind plants. Finally, in the same way that the country proposed the use of continental energy resources, it must do so with the marine energy patrimony development.